1996
DOI: 10.1063/1.363640
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical properties of plasma-deposited a-SiGe:H alloys: Role of growth temperature and postgrowth anneal

Abstract: Basic properties of hydrogenated amorphous silicon-germanium ͑a-SiGe:H͒ alloys deposited by plasma-enhanced chemical-vapor deposition were studied. We found that there is an optimal growth temperature in the range 250-280°C. Infrared-absorption spectra measurements show that in this temperature range the alloys have optimal composition of hydrogen content and bonding, providing a minimum in dangling bond defect density N s and a high photoconductivity ph . Growth at lower temperatures results in hydrogen-rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Although a-(Si,Ge):H is currently the best low bandgap material, it has much poorer electrical and optical properties than a-Si:H. By varying the Ge content in the material, the optical bandgap (Eg) of a-(Si,Ge):H alloy can be modulated from 1.8 eV to I.O eV. Many researchers have found that there is a linear relationship between the Ge content and optical bandgap and the quality of the material degrades with decreasing Eg [5][6][7][8][9][10]. The photoconductivity decreases and dark-conductivity increases when Eg decreases, which causes the decrease of photosensitivity as shown in Figure 1.3.…”
Section: Electrical and Optical Properties Of A-(sige):h Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a-(Si,Ge):H is currently the best low bandgap material, it has much poorer electrical and optical properties than a-Si:H. By varying the Ge content in the material, the optical bandgap (Eg) of a-(Si,Ge):H alloy can be modulated from 1.8 eV to I.O eV. Many researchers have found that there is a linear relationship between the Ge content and optical bandgap and the quality of the material degrades with decreasing Eg [5][6][7][8][9][10]. The photoconductivity decreases and dark-conductivity increases when Eg decreases, which causes the decrease of photosensitivity as shown in Figure 1.3.…”
Section: Electrical and Optical Properties Of A-(sige):h Alloymentioning
confidence: 99%
“…In the past 30 years, hydrogenated amorphous silicon (a-Si:H) and its alloys have attracted more and more interest due to their potential application in solar cells, photo sensors and thin film transistors [1][2][3][4]. Among amorphous silicon alloys, hydrogenated amorphous silicon germanium(a-(Si,Ge):H) has been extensively studied [5][6][7][8][9][10][11] because the bandgap can be easily tuned to be match to the solar spectrum. It can also be used as lower layer in multi-junction solar cells, which have higher energy conversion efficiency than single junction device.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Amorphous silicon is gradually degraded by exposure to light through the Staebler-Wronski effect and hydrogen passivation and alloying this with germanium (the germanium content should not exceed 20 mol% × ≤ 0.20) can reduce both the presence of high-density localized states in the energy gap as well as the film band gap itself. Hence, this can further improve light absorption and stabilize efficiency (Hamakava 1983, Kuznetsov et al 1996, Schropp and Zeman 1998, Budaguan et al 2001, Komp 2002, Horvath et al 2003, Sherchenkov 2003, RosalesQuintero et al 2004. At the same time investigations of H-Si and H-Ge bond concentrations by ESR and IR absorption methods display hydrogen-passivating properties in a-Ge that are even worse than those in a-Si, and therefore, as a whole, the a-Si 0.80 Ge 0.20 :H film photo efficiency turns out to be somewhat lower than that of a-Si:H (Sherchenkov 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous silicon-germanium (a-SiGe:H) alloys have generated a lot of interest both fundamentally and technologically [1][2][3][4][5][6][7][8][9][10][11][12]. By alloying hydrogenated amorphous silicon (a-Si:H) with Ge, it is possible to decrease the band gap and thus improving the long wavelength response of the solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition of thin films for solar cell structure on the low cost and the flexible substrate like plastic foil have necessitated the deposition of the thin films at relatively low temperature. Although many studies [1][2][3][4][5][6][7][8][9][10][11][12] have been undertaken on the a-SiGe:H alloys, very few studies have been made on RF sputtered a-SiGe:H films deposited at relatively low temperature even though the RF sputtering is an useful technique to prepare thin films of amorphous semiconductors and metals [13,14]. In the present manuscript we have studied the RF sputtered a-SiGe:H alloy films deposited at room temperature (RT) onto various substrates including plastic foil and have discussed their properties as the thin film solar cells if fabricated using RT deposited thin films will be of considerable interest in solar cell technology.…”
Section: Introductionmentioning
confidence: 99%